RHETORICAL FACTORS IN SPEECH COMPOSITION ON NOVICE GRAND FINAL NATIONAL UNIVERSITY DEBATE CHAMPIONSHIP (NUDC) 2020 – 2021 - Sherly Alfiani; Ririn Putri Ananda; Yupika Maryansyah; Washlurachim Safitri (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Rhetorical factors in speech composition is an essential element, it is make speech organized and effective. However the most difficult part of speech in debate match is the speeches delivered by each other debater can be accepted logically and clearly both from the july and audience. The objectives of this research to find out the rhetorical factors in speech composition in building speech of debaters on novice grand final NUDC and for the subject of this research are deabters from novice grand final NUDC 2020 – 2021. Rhetorical factors in speech composition consists of 4 components, such as : coherence, unity, emphasis, ethical and inclusive of language. The result show that the debaters on novice grand final NUDC 2020 – 2021 used all component of rhetorical factors in speech, they delivered at the debate match. This implies that the rhetorical factor in speech composition is very important in speech to build strong and believable arguments, especially in developing the style of language in speech itself, it is suggested that in order to be able to make a good rhetorical in speech, so speech can be more organized and effective.